Derivatization of sumanenetrione through Lewis acid-mediated Suzuki–Miyaura coupling and an unprecedented ring opening. Issue 31 (29th March 2023) - Han, Junyi; Uetake, Yuta; Yakiyama, Yumi; Sakurai, Hidehiro
Abstract : A series of sumanenetrione derivatives were synthesized through Lewis acid-mediated Suzuki–Miyaura cross-coupling. They reflected the strong electron-accepting ability of sumanenetrione and the 2-hydroxyphenyl one caused ring open. Abstract : A series of sumanenetrione derivatives were synthesized through Lewis acid-mediated Suzuki–Miyaura cross-coupling. Their optical properties reflected the significantly strong electron-accepting ability of sumanenetrione. The bowl strain of the 2-hydroxyphenyl derivative brought the ring-opening response adjacent to the substituent even at room temperature without any activation, which generally requires harsh conditions.